Prematurity is a critical risk factor for respiratory failure after early inguinal hernia repair under general anesthesia - Schroepf, Sebastian; Mayle, Paulina M.; Kurz, Matthias; Wermelt, Julius Z.; Hubertus, Jochen (Frontiers in Pediatrics, 2022)
Introduction The purpose of this study was to determine the earliest timing of inguinal hernia repair under general anesthesia with minimized risk for respiratory complications during postoperative course. Methods We performed a monocentric analysis of patient records of premature and full-term infants undergoing inguinal hernia repair between 2009 and 2016. In addition to demographic and medical parameters, preexisting conditions and the perioperative course were recorded. Results The study included 499 infants (preterm n = 285; full term n = 214). The number of subsequently ventilated patients was particularly high among preterm infants with bronchopulmonary dysplasia, up to 45.3% (p < .001). Less than 10% of subsequent ventilation occurred in preterm infants after 45 weeks of postmenstrual age at the time of surgery in patients with a body weight of more than 4100 g. Preterm infants with a bronchopulmonary dysplasia had an increased risk of apneas (p < .05). Only 10% of the preterm babies with postoperative apneas weighed more than 3600 g at the time of surgery or were older than 44 weeks of postmenstrual age. Conclusion Our data indicate that after the 45th week of postmenstrual age and a weight above 4100 g, the risk for respiratory failure after general anesthesia seems to be significantly decreased in preterm infants.